Descripción epidemiológica intrahospitalaria de desórdenes vasculares cerebrales - Deza, L.; Aldave, R.; Concha, G.; Salazar, L.; Carmona, J.; Castillo, M.; Rodríguez, A. (Revista de Neuro-Psiquiatría, 2013)
.